LDL-Induced Impairment of Human Vascular Smooth Muscle Cells Repair Function Is Reversed by HMG-CoA Reductase Inhibition - Padró, Teresa (Public Library of Science, 2012)
Growing human atherosclerotic plaques show a progressive loss of vascular smooth muscle cells (VSMC) becoming soft and vulnerable. Lipid loaded-VSMC show impaired vascular repair function and motility due to changes in cytoskeleton proteins involved in cell-migration. Clinical benefits of statins reducing coronary events have been related to repopulation of vulnerable plaques with VSMC. Here, we investigated whether HMG-CoA reductase inhibition with rosuvastatin can reverse the effects induced by atherogenic concentrations of LDL either in the native (nLDL) form or modified by aggregation (agLDL) on human VSMC motility. Using a model of wound repair, we showed that treatment of human coronary VSMC with rosuvastatin significantly prevented (and reversed) the inhibitory effect of nLDL and agLDL in the repair of the cell depleted areas. In addition, rosuvastatin significantly abolished the agLDL-induced dephosphorylation of myosin regulatory light chain as demonstrated by 2DE-electrophoresis and mass spectrometry. Besides, confocal microscopy showed that rosuvastatin enhances actin-cytoskeleton reorganization during lipid-loaded-VSMC attachment and spreading. The effects of rosuvastatin on actin-cytoskeleton dynamics and cell migration were dependent on ROCK-signalling. Furthermore, rosuvastatin caused a significant increase in RhoA-GTP in the cytosol of VSMC. Taken together, our study demonstrated that inhibition of HMG-CoA reductase restores the migratory capacity and repair function of VSMC that is impaired by native and aggregated LDL. This mechanism may contribute to the stabilization of lipid-rich atherosclerotic plaques afforded by statins.